Evaluación técnica del proceso de climatización de salas limpias en Colombia, para Acaire (2019)
The air conditioning of the indoor environment in hospitals includes a series of controls of aspects of air handling and design of environments, which they allow the well-being of the people inside them; these controls must be regulated and standardized according to existing documents and regulations, that need to be improved and controlled in Colombia. Thanks to the identification of the regulations and documentation on clean rooms In hospitals, it was possible to know the way in which the practices of air handling within these, in this case, the selected hospital of the Ciudad de Manizales, through a technical study, it was possible to evaluate the corresponding compliance.